1971
DOI: 10.1677/joe.0.0510465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Testosterone on Glycosaminoglycans in the Prostate, Seminal Vesicles and Salivary Glands of the Rat

Abstract: SUMMARY The effects of castration, and of the daily administration of 100 or 300 μg testosterone propionate (TP) for 1 month to castrated animals, on the glycosaminoglycans of the ventral prostate, seminal vesicles and salivary glands, were studied in male white rats. Castration produced atrophy of the ventral prostate and seminal vesicles together with increased concentration of uronic acid, and atrophy of the submaxillary glands together with decreased uronic acid concentration. The administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In their study the most abundant GAG was DS, a finding that we have confirmed. In the rat ventral prostate GAG are androgen sensitive [22] and in various other tissues, e.g., uterus [23] and aorta [24], GAG are influenced by hormonal manipulations. In view of the suspected role of androgens and oestrogens in the etiology of BPH [25], the effect of hormonal manipulation on human prostatic GAG would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In their study the most abundant GAG was DS, a finding that we have confirmed. In the rat ventral prostate GAG are androgen sensitive [22] and in various other tissues, e.g., uterus [23] and aorta [24], GAG are influenced by hormonal manipulations. In view of the suspected role of androgens and oestrogens in the etiology of BPH [25], the effect of hormonal manipulation on human prostatic GAG would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies have shown that stromal GAGs change during normal development, prostatic hyperplasia, and carcinoma [21-231. The concentration of GAGs in the prostate gland and seminal vesicles of the rat has been shown to change on castration and testosterone ad-ministration after orchidectomy [24]; testosterone has been demonstrated to play a role in the metabolism of GAGs [25]. It has been reported that GAGs are more concentrated at the epithelial-mesenchymal interface where the epithelial morphogenesis is active [26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that prostatic atrophy after castration causes changes in the qualitative and quantitative levels of GAGs and that these changes can be reversed with androgen replacement (Kofoed et al, ; Terry and Clark, ). Moreover, it was observed that the changes are more pronounced in the ventral prostate of rodents than in the dorsal and lateral lobes (Terry and Clark, ).…”
Section: Hormonal Regulation Of the Prostate Glandmentioning
confidence: 99%